Main principles of evidence-based medicine - Кисельов, Сергій Михайлович (Запорізький державний медичний університет, 2020)
In tutorial have been highlighted main issues and principles of evidence-based medicine, determined its role in modern clinical practice. It will be useful for students of medical high schools of III-IV accreditation levels.
Keywords: internal medicine; evidence-based medicine